Low-dose warfarin in atrial fibrillation leads to more thromboembolic events without reducing major bleeding when compared to adjusted-dose - Perret-Guillaume, Christine; Wahl, Denis G. (Thrombosis and Haemostasis, 2004)
The use of warfarin with a range INR of 2.0-3.0 is recommended in prevention of stroke for nonvalvular atrial fibrillation (AF) patients, in particular those older than 75 years. The risk of bleeding that is associated with this range of INR has led to evaluate lower ranges (low-dose or fixed minidose) in terms of risks and benefits. A meta-analysis of all randomized controlled trials evaluating ‘low-intensity’ ‘minidose’ or ‘low-dose anticoagulant’ treatment for prevention of thromboembolic events in AF was conducted by two independent reviewers. Study quality was evaluated in a blinded fashion. Four original studies were retrieved. Outcome events were determined in various treatment groups: ischemic stroke, systemic embolism, thromboses (ischemic stroke, systemic embolism or myocardial infarction), vascular death, major hemorrhage and hemorrhagic death. Results obtained with a random effects model were expressed as a common relative risk. Adjusted-dose warfarin compared with lower dose warfarin (INR ≤1.6) in 2108 randomised patients significantly reduced the risk of any thrombosis: Relative risk (RR): 0.50 (95% CI; 0.25 to 0.97).The RR was 0.46 (95%CI ; 0.2 to 1.07) for ischemic stroke. Inversely lower dose did not statistically decrease the risk for major hemorrhage compared to adjusted-dose: RR adjusted-dose vs lower dose: 1.23 (95% CI ; 0.67-2.27). The RR was 0.97 (95 % CI 0.27-3.54) for hemorrhagic death. Our meta-analysis showed that adjusted-dose compared with low-dose or minidose warfarin therapy (INR ≤1.6) was more effective to prevent ischemic thromboembolic events in patients with atrial fibrillation.
Keywords: Atrial fibrillation; thrombosis; warfarin; low-dose